2012
DOI: 10.1186/1472-6882-12-153
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, genotoxic and antigenotoxic activities of daphne gnidium leaf extracts

Abstract: BackgroundPlants play a significant role in maintaining human health and improving the quality of human life. They serve humans well as valuable components of food, as well as in cosmetics, dyes, and medicines. In fact, many plant extracts prepared from plants have been shown to exert biological activity in vitro and in vivo. The present study explored antioxidant and antigenotoxic effects of Daphne gnidium leaf extracts.MethodsThe genotoxic potential of petroleum ether, chloroform, ethyl acetate, methanol and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 56 publications
1
14
0
1
Order By: Relevance
“…Specifically, the three species selected for this study are rich in essential oils composed mainly of monoterpenes [20,[30][31][32][33]. Daphne gnidium species was selected for its low, although major, concentration of flavonoids [34]. Ruscus aculeatus and Phyllirrea angustifolia species are characterized by their very low content of total phenols [20,35].…”
Section: Selection Of the Studied Plantsmentioning
confidence: 99%
“…Specifically, the three species selected for this study are rich in essential oils composed mainly of monoterpenes [20,[30][31][32][33]. Daphne gnidium species was selected for its low, although major, concentration of flavonoids [34]. Ruscus aculeatus and Phyllirrea angustifolia species are characterized by their very low content of total phenols [20,35].…”
Section: Selection Of the Studied Plantsmentioning
confidence: 99%
“…This protective effect has already been observed elsewhere, using the same experimental approach, with extracts of Cleome rosea (Simões et al, 2006), Daphne gnidium (Chaabane et al, 2012) and Nitraria retusa (Boubaker et al, 2013). The chromatograms obtained from the methanol extract and aqueous fraction of stems, using the method proposed, were insufficient to determine their constituents accurately.…”
Section: Resultsmentioning
confidence: 90%
“…The antigenotoxic effect of S. brasiliensis leaves may be related to their chemical constituents. Flavonoids are described as having antioxidant (Brunetti et al, 2013;Procházková et al, 2011;Romano et al, 2013) and antigenotoxic activities (Boubaker et al, 2013;Chaabane et al, 2012). In addition, flavonoids have antineoplastic effects and can also protect against cardiovascular and neurodegenerative diseases (Obrenovich et al, 2010;Obrenovich et al, 2011;Simões et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of this plant is considered dangerous because of certain toxic effects. Its use can cause headache, paleness, shivers, swelling of the lips and mouth, convulsions, and even death (73). The analysis of the methanol extracts of the branches has shown that the extract has quite good antimicrobial activity, especially against Bacillus lentus and Escherichia coli bacteria.…”
Section: Th E Plant Species Of the Genus Daphne: Pharmacology Screenimentioning
confidence: 99%